Literatura británica del siglo XX y metodología de la enseñanza del inglés desde el trabajo cooperativo - Sierra, Juan Manuel (2014)
This study analizes the views of 52 students of the University of the Basque Country (UPV/EHU), Spain, after their participation in two programmes implemented through cooperative learning projects in the subjects English Language Teaching Methodology and Literature of the second language: English. The data was gathered by means of an anonymous questionnaire which included open and closed questions. The results show the students’ positive attitudes toward cooperative project work and collect the students’ assessments of their educational experience in key aspects of the implementation. Finally, some conclusions and pedagogical implications are presented that can contribute to the effective development of cooperative learning projects.